Why Have Some Farmers Opposed Futures Markets? - Pashigian, B. Peter (Journal of Political Economy, 1988)
A self-interest explanation is presented for opposition by some farm groups to futures markets. During the twenties and thirties political opposition to futures markets was greater in the grain-producing states. The opposition was centered in Minnesota, North Dakota, South Dakota, Montana, and a few other states. The line elevator companies were prominent in these states and not others and used futures prices to facilitate a buying cartel. Futures prices were used to derive a suggested buying price for elevator purchases in each local market. The political opposition to futures by farmers was designed to raise the cost of operating local cartels. Political opposition was greater and gross profit margins of elevators were higher in states with line elevators.